Performance Analysis of Unmanned Aerial Vehicle Assisted Wireless IoT Sensors Based on Air-to-Ground Communication Model for Smart Farming - Sarun Duangsuwan; Sathaporn Promwong (My University, 2023)
We used an unmanned aerial vehicle (UAV) and IoT as a new platform for soil moisture monitoring based on the air-to-ground (A2G) communication model.We investigated an energyefficient UAV trajectory by considering the power outage probability and transmission rate for UAV-assisted wireless IoT sensor connectivity.We considered the closed-form power outage probability for IoT sensors located within the coverage zone of a UAV drone small cell.We conducted experiments in the Napier and Ruzi grass farms with IoT sensors for detecting soil moisture along a drip line irrigation system located in the fields.The power outage probability is given for different UAV heights and transmission rates, which contributes to reliable communication with IoT sensors.
Keywords: Unmanned ground vehicle; E-commerce and Technology Innovations